Digital Transformation of Managerial Accounting - Trends in the New Economic Environment - Florentina Raluca Bîlcan; Ionica Oncioiu; Dumitru Alexandru Stoica; Alina Stanciu (EIRP Proceedings, 2019)
Fluctuations and changes in economic power poles, past financial crises, but also signs of new recession periods, rising capital, multiplying variables and cause-effect factors outline the current economic environment. As an important part of digital transformation, the influence of artificial intelligence in the process of managerial accounting represent the future of taking the best decisions in organizations. The aim of the present study is to explore digital transformation frontiers using the lens of cyber accounting that will help leaders to increase the organizational performance through a clear vision of economic implications of their decisions. The current research contributes both managerial accounting and digital transformation fields by cross-exploring each phenomenon and revealing how digital transformation shape the nature of cyberaccounting as a collaborative research area.